Prevalence of Preeclampsia in Pregnant Women at Dayaku Raja Hospital, Kutai Kartanegara Regency, East Kalimantan, 2018 - Perdana, Edwin; Soenario, Kathleen Juanita Gunawan; Aristida, Steven; Putri, Mutiara Novarinda Iskayati (Jurnal MedScientiae, 2022)
Preeclampsia is a form of syndrome in pregnant women characterized by hypertension andproteinuria that occurs after 20 weeks of pregnancy. Based on data from basic health researchresearched by Anna, the percentage of hypertension in pregnancy in Indonesia is 5% -15%. From theresults of this study, it was found that there was a relationship between age, education and region onthe hypertension research data in pregnant women. This study was conducted at the Dayaku RajaHospital in a descriptive cross-sectional manner, with the aim of identifying pregnant womendiagnosed with preeclampsia, with a population of pregnant women who delivered at the Dayaku RajaHospital. The data studied were parity, age, Gemelli pregnancy, family history of preeclampsia,history of hypertension and education. The prevalence of preeclampsia at Dayaku Raja Hospital in2018 was 49 people (5.5%). It was found that multigravida pregnant women, age category 20-35years, pregnant women without a history of hypertension and last elementary school education weremore likely to experience preeclampsia.